OPTIMALISASI RETRIBUSI PASAR DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH KABUPATEN DOMPU PROVINSI NUSA TENGGARA BARAT - Siregar, Kodir (Jurnal Politik Pemerintahan Dharma Praja, 2018)
ABSTRACT Below Market is one of the main economic’s activator of Dompu’s society. Below Market is located at the urban area in Dompu city so it needs to be manage and arrange in order to keep the society’s Economics consist well. Based on that thing, the writer interest to do a research by a tittle “optimization the levies of below Market in order to increase the local revenue of Dompu regency West Nusa Tenggara province. The purpose of this Research was to determine optimization of a levy Market to increase the local revenue, to know the obstruction factor of managing a levy Market and also to know the efforts that the government do to manage a levy Market. A method that the writer use is descriptive qualitative method using inductive approach. The resource of the data that use is secondary and primary data. To collecting the data the writer do the interview and documentation also use the reduction of data analysis. Presentation and Verification. The Research located at BAPPENDA at Dompu Regency. The result of this research showed that optimization of the levies below Market can not give such a high contribution of the local revenue in Dompu Regency, because the result does not maksimum yet. Besides, the realization of the local revenue still can not reach the target, and the less awareness of the levy payer, and also less of the Supervision in the Regency, less of socialization, less of tool and infrastructure. That it is why we hope that government and the society can support in order to decrease the problem and Gide the Solutions to solven the levies of below Market problems. Keywords: optimization, retribution, local revenue